Contribution of enzymatic properties, cell permeability, and enzyme expression to microbiological activities of beta-lactams in three Bacteroides fragilis isolates that harbor a metallo-beta-lactamase gene. - Rasmussen, B A (1994)
The metallo-beta-lactamase gene, ccrA, has been cloned from three clinical isolates of Bacteroides fragilis, TAL3636, QMCN3, and QMCN4. Although all three isolates harbored a gene encoding a potent beta-lactamase, the MICs of benzylpenicillin, piperacillin, cefotaxime, ceftazidime, imipenem, and biapenem for the three isolates varied from 4- to > 128-fold. QMCN4 was the most susceptible of the three isolates, followed by QMCN3. TAL3636 was resistant to all of the beta-lactams. Previous DNA sequence analysis of the three ccrA genes revealed that the enzymes differed at 5 amino acid residues (B. A. Rasmussen, Y. Gluzman, and F. P. Tally, Mol. Microbiol. 5:1211-1219, 1991). Biochemical characterization of the three enzymes revealed only small differences in kcat and Km values for the majority of beta-lactams tested. Thus, the 5 amino acid substitutions affected the hydrolyzing activity of the enzymes only modestly. Crypticity differences between the three isolates showed that QMCN4 was the least permeable of the isolates to cephaloridine, followed by TAL3636, and that QMCN3 was highly permeable to cephaloridine. Therefore, neither catalytic activity nor permeability was a major contributor to the dramatic differences in the MICs. Instead, microbiological susceptibility was closely related to the level of metallo-beta-lactamase present in each isolate. Both biochemical and physical studies indicated that TAL3636 produced 5- to 10-fold and 50- to 100-fold more metallo-beta-lactamase than QMCN3 and QMCN4, respectively. Therefore, the level of CcrA enzyme production is the dominant contributing factor to high-level resistance among strains harboring a ccrA gene.